Developing high-resolution data to assess spatiotemporal patterns of meteorological drought in India (1981–2021) - Arup Jana (Scientific Reports)
Abstract Climate change has a significant impact on India’s ecosystem and socioeconomic structure, particularly affecting critical sectors such as agriculture and water resources. This study examines the spatiotemporal patterns and seasonality of temperature and precipitation across India from 1981 to 2021. It also investigates trends and the severity of drought events during this period, providing crucial insights for policymakers. Trends and seasonality in air temperature and precipitation were assessed using the European Centre for Medium-Range Weather Forecasts Reanalysis 5th Generation (ERA-5) and Climate Hazards Group InfraRed Precipitation with Station (CHIRPS) data. The Standardized Precipitation Evapotranspiration Index (SPEI) was calculated using the Global Land Evaporation Amsterdam Model and CHIRPS data and validated against Climatic Research Unit (CRU) datasets. Mann–Kendall and Sen’s slope methods were used to analyze drought trends. The analysis was conducted using Google Earth Engine, R, Python, Climate Data Operators, and ArcMap. In this study, SPEI data with a 5 km spatial resolution was developed and validated through correlation maps between the estimated SPEI and CRU-SPEI raster data. The results show rising trends in both temperature and precipitation, with monthly precipitation increasing more sharply at 0.387 mm/year compared to 0.0086 °C/year for temperature. Throughout the study period, regions such as Gujarat, Uttar Pradesh, and parts of the Northeast consistently exhibited lower SPEI values, indicating higher drought susceptibility in these areas. Sen’s slope analysis revealed that from 1981 to 2021, several regions including Rajasthan, western Madhya Pradesh, eastern Uttar Pradesh, Maharashtra, and northern Karnataka exhibited a significant decreasing trend in SPEI, indicating intensifying and more frequent drought conditions. These findings highlight the growing impact of climate change in India, evidenced by rising temperatures, changing precipitation patterns, and increasing droughts, emphasizing the urgent need for adaptive measures and informed policy interventions to address these climatic challenges.